Relationships between Trust and Collaborative Culture in The Context of Tacit Knowledge Sharing - Wioleta Kucharska (Journal of Entrepreneurship, Management and Innovation)

(untitled)
The literature review presents a lot of theoretcal and empirical evidence that trust afects collaboratve culture. The opposite also proves to be true: collaboratve culture infuences trust. The main hypothesis presented in this paper says that both these factors are strongly correlated and modify each other. This study examines the mutual relatonship of the said variables in the context of tacit knowledge sharing based on research conducted among 514 Polish professionals performing diferent functons, and having various experience in managing projects, in the constructon industry. The results obtained in the course of the study indicate that there is not only a strong correlaton between trust and collaboratve culture but both of them have a strong infuence on tacit knowledge sharing. The main managerial implicaton of the study is the importance of stmulatng the growth of both collaboratve culture and trust. receiving a strong synergy efect will make it possible to leverage tacit knowledge sharing as an agent contributng to a company’s performance.